2012
DOI: 10.1016/j.bjps.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The safety of autologous fat transfer in breast cancer: Lessons from stem cell biology

Abstract: Autologous fat grafting is versatile tool in plastic surgery and is increasing used for reconstruction following breast conserving surgery for breast cancer. Part of the reconstructive qualities of the transferred fat may be due to the presence of adipose derived mesenchymal stem cells (ADMSC) playing an angiogenic and an adipogenic role. In this context it must be considered if autologously engrafted fat tissue could contribute to carcinogenesis following breast conserving surgery. In this article we review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 46 publications
1
59
0
11
Order By: Relevance
“…Coleman attempted to resolve these fears, by advocating meticulous planning, 'atraumatic liposuction', centrifugation and graft placement to provide 'pure, intact parcels of fat' to encourage integration and long-term graft survival 1,6,7,10,11,15,16 . He also became interested in the mechanisms of fat graft survival and stability, and postulated whether Fat is a metabolically active tissue consisting of a heterogeneous cell population secreting cytokines, hormones and growth factors [56][57][58][59] . A fat graft specimen contains mature adipocytes and preadipocytes, also known as adipose derived stem cells (ASC) 56,58,59 .…”
Section: Commented [Re8]: Are These Figure Pooled Results Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Coleman attempted to resolve these fears, by advocating meticulous planning, 'atraumatic liposuction', centrifugation and graft placement to provide 'pure, intact parcels of fat' to encourage integration and long-term graft survival 1,6,7,10,11,15,16 . He also became interested in the mechanisms of fat graft survival and stability, and postulated whether Fat is a metabolically active tissue consisting of a heterogeneous cell population secreting cytokines, hormones and growth factors [56][57][58][59] . A fat graft specimen contains mature adipocytes and preadipocytes, also known as adipose derived stem cells (ASC) 56,58,59 .…”
Section: Commented [Re8]: Are These Figure Pooled Results Frommentioning
confidence: 99%
“…He also became interested in the mechanisms of fat graft survival and stability, and postulated whether Fat is a metabolically active tissue consisting of a heterogeneous cell population secreting cytokines, hormones and growth factors [56][57][58][59] . A fat graft specimen contains mature adipocytes and preadipocytes, also known as adipose derived stem cells (ASC) 56,58,59 . ASCs have considerable angiogenic and antiapoptotic features and constitute 10% of the cell population, however graft survival is largely dependent on them given their huge proliferative contribution 14,40,[57][58][59] .…”
Section: Commented [Re8]: Are These Figure Pooled Results Frommentioning
confidence: 99%
See 1 more Smart Citation
“…A utologous fat grafting is widely used in plastic surgery to restore contour, increase volume and improve irradiated skin in breast reconstructive surgery [1][2][3][4] . The risk of tumor recurrence is unknown when this type of reconstruction is performed simultaneously to conservative surgery, because there are no studies in the literature that use this method in the immediate breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have shown ADSCs may either present as a source of tumor or provide an environment for the growth of the tumor, lipofilling combined with ADSCs and ADSCs based breast tissue engineering has been greatly impeded. [53][54][55] Another type of cells in the adipose tissue, SVF, may present as an alternative, however, studies are still needed to verify its safety. [56] Since still there has not been enough evidence showing that these techniques can indeed cause tumor clinically and great progress is still achieving in the understanding of cancer and stem cells, breast tissue engineering may still regain its prospect in the future.…”
Section: Stem Cells and Breast Tissue Engineeringmentioning
confidence: 99%